2010
DOI: 10.1002/elps.200900496
|View full text |Cite
|
Sign up to set email alerts
|

Determination of haloacetic acids in water using solid‐phase extraction/microchip capillary electrophoresis with capacitively coupled contactless conductivity detection

Abstract: Haloacetic acids (HAAs) were determined by a fast and simple analysis method based on microchip electrophoresis and capacitively coupled contactless conductivity detection (C(4)D). Two chlorinated acetic acids, dichloroacetic acid (DCAA) and TCA were detected in swimming pool water. Different BGEs were tested, and sodium carbonate was selected as BGE for the separation and detection in the reported experiments. Additionally, pH values and concentrations of carbonate buffer were optimized. The response times fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…For example, in the field of water analysis only a limited number of relevant papers can be found [7,16,[24][25][26][27]32]. Bodor et al [7] reported on isotachophoresis (ITP) determination of chloride, nitrate, sulfate, nitrite, fluoride and phosphate at pH 3.5 on a poly(methylmethacrylate) (PMMA) microchip using contact conductivity detection.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, in the field of water analysis only a limited number of relevant papers can be found [7,16,[24][25][26][27]32]. Bodor et al [7] reported on isotachophoresis (ITP) determination of chloride, nitrate, sulfate, nitrite, fluoride and phosphate at pH 3.5 on a poly(methylmethacrylate) (PMMA) microchip using contact conductivity detection.…”
Section: Introductionmentioning
confidence: 98%
“…On-line ITP treatment of tap, mineral and river waters contributed for sensitive MCE determination of minor anions (with LOD in the range 9.6-66.5 μg L -1 ) and analysis lasted for 4-6 min. Haloacetic acids were determined in swimming pool water by MCE and capacitively coupled contactless conductivity detection at pH 10 in 3 min [32]. LOD for di-and trichloroacetic acids after solid-phase extraction and clean-up were 38 and 62 μg L -1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water utilities without expert personnel and high-end technology face the challenge of minimizing HAAs formation in drinking water treatment systems with few choices for real-time analysis. Alternatives to MS-based analysis have been reported using solid phase extraction (SPE) with CE to analyze HAAs at high levels (greater than 50 lg L À1 ) in swimming pools (Ding and Rogers, 2010), midlevels (6-12 lg L À1 ) (Kubáň et al, 2012), and low levels (less than 5 lg L À1 ) (Bernad et al, 2011). SPE has also been used with 2-D ion chromatography with membrane suppressed conductivity detection (IC-MSCD) (Verrey et al, 2013) and UPLC with UV absorbance (Nsubuga and Basheer, 2013) for HAAs analysis in drinking water and swimming pools, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, HAAs preconcentration has used techniques such as liquid-liquid extraction (USEPA, 1995(USEPA, , 2003Hammami and Driss, 2013;Liu et al, 2013) or solid phase extraction Paull and Barron, 2004;Ding and Rogers, 2010;Prieto-Blanco et al, 2012;Kubáň et al, 2012;Nsubuga and Basheer, 2013) via manual or semi-automated analysis. For continuous, on-line, real-time analysis, an automated preconcentration module must do all of the sample handling and preparation steps for SPE preconcentration from sample intake and acidification to elution onto the analyzer for injection.…”
Section: Introductionmentioning
confidence: 99%